Recent Technical Advances in Accelerating the Clinical Translation of Small Animal Brain Imaging: Hybrid Imaging, Deep Learning, and Transcriptomics - Ren, Wuwei; Ji, Bin; Guan, Yihui; Cao, Lei; Ni, Ruiqing (Frontiers in Medicine, 2022)
Small animal models play a fundamental role in brain research by deepening the understanding of the physiological functions and mechanisms underlying brain disorders, and thus are essential in the development of therapeutics and diagnostic imaging tracers targeting central nervus system. The advances in structural, functional and molecular imaging using magnetic resonance imaging, positron emission tomography, fluorescence imaging and optoacoustic imaging have enabled the interrogation of the rodent brain across a large temporal and spatial resolution scale in a non-invasively manner. However, there are still several major gaps in translating from preclinical brain imaging to the clinical setting. The hindering factors include: 1) intrinsic differences between biological species regarding brain size, cell type, protein expression level, and metabolism level, and 2) imaging technical barriers regarding interpretation of image contrast, and limited spatiotemporal resolution. To mitigate those factors, transcriptomics, single cell sequencing and measures to identify the cellular source of PET tracers have been developed. Meanwhile, hybrid imaging techniques that provide highly complementary anatomical and molecular information are emerging. Furthermore, deep learning based image analysis have been developed to enhance the quantification and optimization of the imaging protocol. In this mini review, we summarize the recent developments in small animal neuroimaging towards improved translational power, with a focus on technical improvement including hybrid imaging, data processing, single cell sequencing, and on-chip pharmacokinetics. We also discuss outstanding challenges, considerations towards increasing translational power and propose future outlooks.